Cyclophosphamide induction dose and outcomes in ANCA-associated vasculitis with renal involvement: a comparative cohort study - Speer, Claudius; Altenmüller-Walther, Christine; Splitthoff, Jan; Nußhag, Christian; Kälble, Florian; Reichel, Paula; Morath, Christian; Zeier, Martin; Bergner, Raoul; Schaier, Matthias (Medicine, 2021)
Treatment of ANCA-associated vasculitis (AAV) improved over the last decades but disease-unspecific agents such as cyclophosphamide are still associated with serious adverse events, including high rates of infectious complications and malignancy with increased mortality. In this comparative cohort study, we included 121 AAV patients with renal involvement from 2 German vasculitis centers. Patients were separated into subsequent groups: 2.5 to 3 g vs >3 g cumulative cyclophosphamide induction dose. We investigated if a cyclophosphamide induction dose of 2.5 to 3 g could maintain efficacy while minimizing adverse events in AAV patients with renal involvement. Patients with 2.5 to 3 g vs >3 g cumulative cyclophosphamide (median 3.0 g vs 5.5 g, P < .001) had a comparable time to remission (median 4.0 vs 3.8 months, log-rank P = .87) with 90.6% and 91.5% achieving remission after 12 months. Refractory disease was low in both groups (median 3.6% vs 6.2%, P = .68) and relapse rate did not differ (median 36% vs 42%, log-rank P = .51). Kidney function was comparable at disease onset in both groups (eGFR, mean +/- SD 29 +/- 20 mL/min/1.73 m(2) vs 35 +/- 26 mL/min/1.73 m(2), P = .34) and improved after 2 years irrespective of the cyclophosphamide dose (Delta eGFR, mean +/- SD +8.9 +/- 1.4 mL/min/1.73 m(2) vs +6.0 +/- 1.1 mL/min/1.73 m(2), P = .33). The 2.5-3 g group had a lower rate of leukopenia (HR = 2.73 [95% CI, 1.2-6.3], P = .014) and less infectious episodes per patient (median 1.2 vs 0.7, P = .012), especially urinary tract infections (HR = 2.15 [95% CI, 1.1-4.5], P = .032). A cyclophosphamide induction dose of 2.5 to 3 g was able to induce remission and prevent from relapses with fewer cases of leukopenia and less infectious episodes during follow-up. Especially elderly AAV patients who are particularly susceptible to infectious complications could benefit from minimizing dosing regimens with maintained efficacy to control disease activity.